(untitled) (Tempo e Argumento, 2023)
This article presents the results of a research on the configurations of memory in high school students in the city of Valparaíso. The conceptions of history, memory and historical narratives of political conflicts in the recent history of Chile (1965-2017) were approached through a case study methodology and focus groups in which students from five public schools finishing their secondary education participated. The discursive analysis of memory elaborations shows historical narrative patterns about the recent past shaped by dehistoricized, fragmented, polarized and romantic visions of history, strongly influenced by power, inequalities and popular memory. In the final part, we reflect on the incidence of these narrative configurations in the relationship with the past in the new generations and their effects on their political dispositions.